Kyrgyz Turks’ Proverbs in The Context of Language and Word - Gökbayır, Tuğba (Ahmet BURAN, 2022)
One of the common language and cultural elements among Turkic communities is our adages. Adages are stereotypes words that give advice in short and concise. Proverbs in a language are words that can maintain the society's worldview, experiences, culture and traditions, and expressive power for centuries. Proverbs can be transmitted for centuries without changing; sometimes it changes or disappears completely. Like idioms, proverbs can survive in dialects of the same language. Adages in the whole Turkic World spread over a wide area and reflect the common history and culture of the Turks. In this study, the proverbs of the Kyrgyz Turks, one of the important tribes of the Turkic world, about language and speech are discussed. The proverbs are taken from the book named “Kırgız Makal Lakaptarı” published in Kyrgyzstan in 1982. The role and importance of language in society will be evaluated. In the examined proverbs, the purposes for which language and speech are taken will be shown in the form of sub-headings.

Türk toplulukları arasında ortak dil ve kültür unsurlarından biri atasözlerimizdir. Atasözleri, kısa ve özlü sözlerle öğüt veren kalıplaşmış sözlerdir. Bir dilin içerisinde yer alan atasözleri, toplumun dünya görüşünü, deneyimlerini, kültür ve geleneklerini, anlatım gücünü yüzyıllar boyunca devam ettirebilen sözlerdir. Atasözleri, kimi zaman değişime uğramadan yüzyıllar boyu aktarılabilir; kimi zaman da değişikliğe uğrar ya da tamamen kaybolur. Deyimler gibi atasözleri de, aynı dilin lehçelerinde varlığını sürdürebilir. Bütün Türk Dünyasındaki atasözleri, geniş bir alana yayılarak Türklerin ortak tarihini, kültürünü ve dilini yansıtır. Bu çalışmada, Türk dünyasının önemli boylarından Kırgız Türklerinin dil ve söz ile ilgili atasözleri ele alındı. Atasözleri, 1982 yılında Kırgızistan’da basılan “Kırgız Makal Lakaptarı” adlı kitaptan alındı. Dilin toplum içindeki rolü ve önemi değerlendirilecektir. İncelenen atasözlerinde, dil ve sözün hangi amaçlar için ele alındığı alt başlıklar şeklinde gösterilecektir.
DİL VE SÖZ BAĞLAMINDA KIRGIZ TÜRKLERİNİN ATASÖZLERİ
Keywords: Linguistics; Dilbilim